Nano-silica added to Portland cement - Mendes, Thiago Melanda; Repette, Wellington Longuini (Acta Scientiarum. Technology, 2021)
For a controlled particle size distribution, nano-silica was added to three different cements. The chemical and mineralogical compositions of the cements were characterized by fluorescence and X-ray diffraction. The granulometric distributions of cements and nano-silicas were obtained by laser granulometry and dynamic lightning scattering. The specific surface area of the raw materials was determined by gas adsorption. The effect of nano-silica and type of cement on rheological behavior was evaluated by rotational rheometry. The mechanical performance was investigated through the compression strength. The microstructural analysis was performed by scanning electron microscopy. The water demand and the consumption of dispersant increases according to the nano-silica content. The reduction in the inter-particle separation, and the agglomeration of nano-silica led to an increase in the viscosity of the suspension. The mechanical performance was directly affected by the specific surface area of the cements. Microstructural analysis showed that nano-silica changed from a layered adsorbed structure, to a porous or agglomerated structure.